2019
DOI: 10.1088/1361-6560/ab083a
|View full text |Cite
|
Sign up to set email alerts
|

Combining many-objective radiomics and 3D convolutional neural network through evidential reasoning to predict lymph node metastasis in head and neck cancer

Abstract: Lymph node metastasis (LNM) is a significant prognostic factor in patients with head and neck cancer, and the ability to predict it accurately is essential to optimizing treatment. Positron emission tomography (PET) and computed tomography (CT) imaging are routinely used to identify LNM. Although large or highly active lymph nodes (LNs) have a high probability of being positive, identifying small or less reactive LNs is challenging. The accuracy of LNM identification strongly depends on the physician's experie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 37 publications
1
63
1
2
Order By: Relevance
“…In our previous study, we identified several advantages of our multi-objective, multi-modality, and multi-classifier radiomics model for some outcome prediction applications, such as predicting DM in HNSCC, non-small cell lung cancer, and cervical cancer. 12,29,43,44 However, the previous approaches focused on only one or two of the aspects in the current mCOM, such as a multi-objective model trained with features from a single modality, 44 or a multi-modality model built with a single classifier. 29 In addition, these approaches also required that the best solution be selected manually from the Pareto-optimal solution set for the final prediction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, we identified several advantages of our multi-objective, multi-modality, and multi-classifier radiomics model for some outcome prediction applications, such as predicting DM in HNSCC, non-small cell lung cancer, and cervical cancer. 12,29,43,44 However, the previous approaches focused on only one or two of the aspects in the current mCOM, such as a multi-objective model trained with features from a single modality, 44 or a multi-modality model built with a single classifier. 29 In addition, these approaches also required that the best solution be selected manually from the Pareto-optimal solution set for the final prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomics-based methods have shown promising performance in HNSCC-related tasks, such as treatment outcome prediction, tumor segmentation, and pathologic classification. [7][8][9][10][11][12] These methods extract handcrafted quantitative features from radiological images, then use machine learning tools to analyze these features and build predictive models. Parmar et al extracted radiomics features from pretreatment X-ray computed tomography (CT) images and built a Cox and logistic regression model for predicting local tumor control (LC) after chemoradiotherapy of HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…In Reference [ 58 ], Nie et al proposed a multi-channel structure of 3D CNN for survival time prediction of Glioblastoma patients using multi-modal head images (T1 weighted MRI and diffusion tensor imaging, DTI). Recently, in Reference [ 82 ], the author presented a hybrid model for the classification and prediction of lymph node metastasis (LNM) in head and neck cancer. They combined the outputs of MaO-radiomics and 3D CNN architecture by using an evidential reasoning (ER) fusion strategy.…”
Section: Applications In 3d Medical Imagingmentioning
confidence: 99%
“…Future prospective studies will show whether these results can also be achieved in people, but the approach seems promising. Another group achieved promising results in the detection of micrometastases in lymph nodes in head and neck cancers by combining radiomics analysis of CT data and 3-dimensional CNN analysis of 18 F-FDG PET data through evidential reasoning (55).…”
Section: Reportingmentioning
confidence: 99%